PRINCIPAL COMPONENT ANALYSIS OF FACTORS DETERMINING PHOSPHATE ROCK DISSOLUTION ON ACID SOILS - Hilman, Yusdar; Rahim, Anuar Abdul; Musa, Mohamed Hanafi; Hashim, Azizah (Indonesian Agency for Agricultural Research and Development - MOA, 2007)
Many of the agricultural soils in Indonesia are acidic and lowin both total and available phosphorus which severely limits theirpotential for crops production. These problems can be correctedby application of chemical fertilizers. However, these fertilizersare expensive, and cheaper alternatives such as phosphate rock(PR) have been considered. Several soil factors may influencethe dissolution of PR in soils, including both chemical and physicalproperties. The study aimed to identify PR dissolution factorsand evaluate their relative magnitude. The experiment was conductedin Soil Chemical Laboratory, Universiti Putra Malaysia andIndonesian Center for Agricultural Land Resources Research andDevelopment from January to April 2002. The principal componentanalysis (PCA) was used to characterize acid soils in anincubation system into a number of factors that may affect PRdissolution. Three major factors selected were soil texture, soilacidity, and fertilization. Using the scores of individual factors asindependent variables, stepwise regression analysis was performedto derive a PR dissolution function. The factors influencing PRdissolution in order of importance were soil texture, soil acidity,then fertilization. Soil texture factors including clay content andorganic C, and soil acidity factor such as P retention capacityinteracted positively with P dissolution and promoted PR dissolutioneffectively. Soil texture factors, such as sand and siltcontent, soil acidity factors such as pH, and exchangeable Cadecreased PR dissolution.